Pengaruh Kepemilikan Institusional, Karakteristik Dewan Komisaris, Pengungkapan Manajemen Resiko Terhadap Keberadaan Komite Manajemen Resiko (International Forum of Researchers and Lecturers, 2024)
This study aims to examine and analyze the influence of institutional ownership, characteristics of the board of commissioners on risk management disclosures on the existence of a risk management committee (RMC). The population in this study are mining companies and various industries listed on the IDX in 2021, namely 102 companies. The sampling technique uses a purposive sampling method and the results are only 45 companies that are included in the sample criteria. Data analysis technique uses logistic regression. The test results show that institutional ownership and independent commissioners have no effect on the existence of a risk management committee (RMC), while education, experience and disclosure of risk management have an effect on the presence of a risk management committee (RMC). These results indicate that risk management should be carried out by the company to develop a follow-up strategy so that business continuity is maintained under the supervision of the board of commissioners and included in the company's annual report.